PRESEPSI DEVELOPER PROPERTI SYARI'AH TERHADAP PEMBIAYAAN KPR AKAD MURABAHAH PADA PERBANKAN SYARI'AH DI KOTA KENDARI - Pilo, Fandy Izmi; Mahfudz, Mahfudz (IAIN Kendari, 2023)
This study aims to analyze the perceptions of property developers towards the practice of murabaha contract KPR financing in Islamic banking in Kendari City. Qualitative research with an explanatory approach with an in-depth interview method with informants, namely Islamic property developers who run a house buying and selling business in Kendari city, resulted in research conclusions showing that Islamic property developers perceive the practice of murabaha contract KPR financing in Islamic banking to contain several problems. From the aspect of the perpetrator, it is considered that it does not fulfill the pillars of buying and selling; when the transaction agreement, the fact that a house has been sold that has not been owned, financing by the bank is more accurately called a loan contract than a sale and purchase so that the margin is more like usury; the use of the house (the object of buying and selling) as collateral has violated the principle of transferring ownership; late fees are the same as usury; and the application of life and fire insurance contains gharar, speculation, violates the principles of tabarru' and dhaman, and there are two contracts in one transaction.